PENGARUH WHISTLEBLOWING SYSTEM DAN FAKTOR LAINNYA PADA INTEGRITAS LAPORAN KEUANGAN - Jennyver, Jennyver; Mungniyati, Mungniyati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The objective of this research is to obtain empirical evidence regarding variables influencing the integrity of financial statements. Specifically, institutional ownership, managerial ownership, independent commissioners, audit tenure, whistleblowing system, leverage, and company size on integrity financial statements. The population used in this study consists of companies in the cyclicals and non-cyclicals consumer sectors listed on the Indonesia Stock Exchange (IDX) from 2020 until 2022. Sample selection was conducted using purposive sampling method, resulting in 543 data samples or 181 companies meeting the sample selection criteria. The collected sample data were tested and analyzed using multiple regression analysis. The findings of this research indicate that institutional ownership and leverage affect the integrity of financial statements. Meanwhile, managerial ownership, independent commissioners, audit tenure, whistleblowing system, and company size do not have a significant impact on the integrity of financial statements.